Cultural Integration and Export Variety Overlap Across Countries - Peter Egger; Andrea Lassmann (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper assesses the role of a larger degree of common language use between the populations of two countries on the so-called extensive product margin of trade. We focus on the overlap of products exported or imported between any pair of countries. The results suggest that the effect of varying aspects of sharing a common language on the variety overlap is both positive and important. The effect of sharing a common spoken language exceeds the one of common native language, implying that a larger overlap in language proficiency is quantitatively more important than a higher cultural proximity.
Keywords: C31; F14; F15; Z10; 330; common language; international trade; trade costs; cultural integration